1997
DOI: 10.1021/jf960508e
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Origin of the Aroma Impact Compounds of Yogurt Flavor

Abstract: Yogurt exhibits a delicate and low intense flavor which requires mild sample isolation techniques and sensitive identification means. This paper decribes the application of two new flavor separation techniques:  combined static and dynamic headspace, and preparative simultaneous distillation−extraction under vacuum. Of the 91 components identified by mass spectrometry, 21 were found to have a major impact on the aroma using a new method for the treatment of GC−sniffing data. One of these compounds, 1-nonen-3-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
178
2
9

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(198 citation statements)
references
References 21 publications
9
178
2
9
Order By: Relevance
“…Lactic acid and formic acid could be detected as distinct peaks in our HPLC analysis with retention times of 4.3 and 4.9 min, respectively. The main flavoring agent in yogurt is lactic acid, which contributes to its sour and refreshing taste (Ott et al, 1997).…”
Section: Changes In Acetaldehyde Diacetyl Lactic Acid and Formic Acmentioning
confidence: 99%
“…Lactic acid and formic acid could be detected as distinct peaks in our HPLC analysis with retention times of 4.3 and 4.9 min, respectively. The main flavoring agent in yogurt is lactic acid, which contributes to its sour and refreshing taste (Ott et al, 1997).…”
Section: Changes In Acetaldehyde Diacetyl Lactic Acid and Formic Acmentioning
confidence: 99%
“…diacetylactis and Leuconostoc sp, which are used for the production of cultured 49 cream, cultured butter, buttermilk and fresh cheeses. Diacetyl is also a key aroma compound 50 in yogurt (Imhof et al, 1995;Ott et al, 1997), but in this case, it is mainly produced by 51…”
Section: Introduction 45 46mentioning
confidence: 99%
“…Ott et al [36] identified 91 aroma compounds (GC-olfactometry) in yoghurt among which 21 w e r e d e t e c t e d m o r e f r e q u e n t l y a n d w o u l d t h u s h a v e a m a j o r i m p a c t o n f l a v o u r . Acetaldehyde is found in significant quantities and is responsible for the characteristic smell of yoghurt.…”
Section: A Look At Yoghurt Aroma Compoundsmentioning
confidence: 99%
“…Acetaldehyde is found in significant quantities and is responsible for the characteristic smell of yoghurt. Diacetyl, pentane-2,3-dione, and dimethyl sulphide also have a major impact on yoghurt flavour [36,37].…”
Section: A Look At Yoghurt Aroma Compoundsmentioning
confidence: 99%